How families facilitate the development of empathy in children: a family systems theory perspective - Kaufman, Mark (Kansas State University, 2011)
Abstract This study seeks to clarify a controversy in the literature about which characteristics of families are most responsible for facilitating the development of empathy in children. The study utilized a correlational research design and self-report questionnaires. The Balanced Emotional Empathy Scale measured the criterion variable, subjects’ levels of emotional empathy. The Circumplex Model of Marital and Family Systems’ accompanying questionnaire, the fourth version of the Family Adaptability and Cohesion Evaluation Scales (FACES IV) measured the two key predictor variables, levels of family cohesion and family flexibility, in the subjects’ families of origin. The central hypothesis of the Circumplex Model is that healthy family functioning would be predicted by balanced functioning on both of these key dimensions of family life. The first predictor variable, family cohesion, appears to encompass those factors emphasized by researchers who have asserted that positive family affective bonds would be the family characteristic most predictive of higher levels of empathy in children. The second predictor variable, family flexibility, appears to encompass those factors emphasized by researchers who have asserted that the style of parental discipline would be the family characteristic most predictive of higher levels of empathy in children. Participants in this study were all students at a mid-size, public, Midwestern university. A purposive convenience sample was utilized. Correlational statistics and multiple regression analyses were used to test hypotheses. The results suggested several conclusions. Balanced levels of family cohesion were positively associated with higher levels of emotional empathy, as predicted. The prediction that balanced levels of family flexibility would also be positively associated with higher levels of emotional empathy was not supported. Instead, higher levels of empathy were associated with a somewhat strict or rigid style of parental discipline. Various alternative explanations for these results are discussed, as are limitations of the study, recommendations for future research, and implications for practitioners.
Keywords: Circumplex Model of Marital and Family Systems; Balanced Emotional Empathy Scale; Empathy; Family flexibility; Family cohesion; Individual & Family Studies (0628)